2021
DOI: 10.1177/0272989x211053563
|View full text |Cite
|
Sign up to set email alerts
|

A Game Theoretic Analysis of Competition Between Vaccine and Drug Companies during Disease Contraction and Recovery

Abstract: Background Infectious diseases such as COVID-19 and HIV/AIDS are behaviorally challenging for persons, vaccine and drug companies, and donors. Methods In 3 linked games in which a disease may or may not be contracted, [Formula: see text] persons choose risky or safe behavior (game 1). Two vaccine companies (game 2) and 2 drug companies (game 3) choose whether to develop vaccines and drugs. Each person chooses whether to buy 1 vaccine (if no disease contraction) or 1 drug (if disease contraction). A donor subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, the work of Hausken (2018) has shown that symbolic value is another important component of a target's value, which can open up the possibility of studying the impact of pandemics on a target's symbolic value. Moreover, in future research, a richer conceptualization of a target's valuation during a pandemic is to assume that it is also impacted by vaccines and drugs (which can ameliorate or eliminate the infection and thus how populations flow), as well as the interactions among persons, vaccine and drug companies (Hausken & Ncube, 2022). Finally, our model is formulated in a pandemic situation, and is a first step in modeling counterterrorism resource allocation when target valuations are subject to change.…”
Section: Discussionmentioning
confidence: 99%
“…However, the work of Hausken (2018) has shown that symbolic value is another important component of a target's value, which can open up the possibility of studying the impact of pandemics on a target's symbolic value. Moreover, in future research, a richer conceptualization of a target's valuation during a pandemic is to assume that it is also impacted by vaccines and drugs (which can ameliorate or eliminate the infection and thus how populations flow), as well as the interactions among persons, vaccine and drug companies (Hausken & Ncube, 2022). Finally, our model is formulated in a pandemic situation, and is a first step in modeling counterterrorism resource allocation when target valuations are subject to change.…”
Section: Discussionmentioning
confidence: 99%